Broadband Multilayered Array Antenna with EBG Reflector - P. Chen; X. D. Yang; C. Y. Chen; Z. H. Ma (International Journal of Antennas and Propagation)
Most broadband microstrip antennae are implemented in the form of slot structure or laminate structure. The impedance bandwidth is broadened, but meanwhile, the sidelobe of the directivity pattern and backlobe level are enlarged. A broadband stacked slot coupling microstrip antenna array with EBG structure reflector is proposed. Test results indicate that the proposed reflector structure can effectively improve the directivity pattern of stacked antenna and aperture coupled antenna, promote the front-to-back ratio, and reduce the thickness of the antenna. Therefore, it is more suitable to be applied as an airborne antenna.